Intensified Assisted Partner Notification Implementation in Botswana Increased Partner Identification but Not HIV Case-Finding: Findings Highlight the Need for Improved Data Monitoring. (1st July 2021) - Grande, Matias; Mawandia, Shreshth; Bakae, Odirile; Tau, Lenna; Mogomotsi, Goabaone P.; Ngombo, Modise; Norman, Tebogo; Ledikwe, Jenny; Golden, Matthew R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: How to implement and monitor assisted partner services (APS) programs for HIV infection as they go to scale-up is uncertain. Setting: Forty Botswana Ministry of Health clinics, 2018–2020. Methods: We compared 2 APS implementation phases. During phase 1, training, supervision, and data collection were minimal; only newly diagnosed HIV-positive persons received APS, and APS recipients notified partners themselves or jointly with counselors. Phase 2 included the following: intensified training and supervision; APS provision to previously diagnosed, untreated persons; structured interview records; and counselors offering to notify partners directly. Results: Five thousand one hundred seventy-five and 1265 newly diagnosed HIV-positive persons received APS in phases 1 and 2, respectively. Comparing the phases, program reach (percentage of newly diagnosed cases receiving APS) increased from 86% to 93%, the contact index (sex partners named per case) increased from 0.85 to 1.32, and the percentage of cases with an identified HIV-positive partner increased from 12.6% to 60% ( P < 0.001, all outcomes). The testing index (partners tested per case) was higher in phase 1 (0.56 vs. 0.45, P = 0.05), whereas the case-finding index (partners testing HIV-positive per case) did not change (0.13 vs. 0.14, P = 0.50). Five hundred seventy-eight (76%) of 756 HIV-positive partners in phase 2 were previously diagnosed; cases identified only 15% of these partners as HIV-positive at their initial interview. Conclusions: APS scale-up increased reach, the contact index, and the identification of previously diagnosed sex partners but not HIV case-finding. Improved, more comprehensive data likely explain the absence of increased case-finding, highlighting the need for more comprehensive data collection.